Report to the President and the Congress on significant market opening (Office of the Trade Representative WashingtonUS, 1994)
Provides a review of major developments that affect U.S. trade with countries and regions that meet the criteria set out in Section 108 of the NAFTA implementing legislation. Supplies economic data on U.S. trading partners, ranked by U.S. exports for 1993 and GDP for 1991, and showing their share of exports to the United States in 1992. Covers all regions of the world and selected countries and provides additional detail on Latin America and the Asia/Pacific regions.
DC